Anti-aging lamp shell composite material and preparation method thereof
By using modified PC masterbatches, modified ABS masterbatches, titanium silicon powder and hollow glass microbeads in the lamp housing, the problem of degradation of light transmittance and reflective performance caused by aging of the lamp housing is solved, and the effect of improving light reflectivity and delaying aging is achieved.
Patent Information
- Application Number
- CN202411887490.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-11
AI Technical Summary
Existing lamp housing materials are prone to aging during long-term use, resulting in a decrease in light transmittance and reflective properties, a decrease in light output and an overall illuminance.
It adopts an anti-aging lamp housing composite material, including modified PC masterbatch, modified ABS masterbatch, titanium silicon powder and hollow glass microbeads, and improves the antioxidant performance of the material through modified resin and ultraviolet absorbers, and improves the light reflectivity through titanium silicon powder and hollow glass microbeads.
It effectively improves the light reflectivity of the lamp housing, reduces the light absorption, delays the aging process of the lamp housing, and improves the overall luminous flux and service life of the lamp.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lamp housing materials, and in particular to an anti-aging lamp housing composite material and a preparation method thereof. Background Art
[0002] The quality of eye-protection classroom lights will directly affect students' vision. Some schools will report that classroom lights are not bright enough after being used for a long time, and the lamp shell turns yellow and brittle. The outer shell of the lamp is generally made of plastic materials such as PC or PS. LED lamp beads will heat up when in use. The outer shell of the lamp is exposed to heat and light for a long time during use. The plastic material is easy to age and turn yellow. After the lamp shell ages and turns yellow, the light transmittance and reflective performance are greatly reduced, resulting in a decrease in the amount of light output and a decrease in the overall illumination of the classroom lamp.
[0003] There are some modified anti-aging plastics in the prior art, but the lamp is constantly exposed to light during long-term use, and the lamp housing absorbs a large amount of light, so it is still relatively easy to age. Summary of the invention
[0004] In view of the above problems, the present invention aims to solve the above problems. One object of the present invention is to provide an anti-aging lamp housing composite material and a preparation method to solve the above problems, effectively increase the reflection effect of the lamp housing, improve the luminous flux of the lamp, and reduce the absorption of light by the lamp housing, thereby slowing down the aging of the lamp housing.
[0005] The scheme adopted by the present invention is: an anti-aging composite material for lamp housing, the components by mass fraction include: 80-110 parts of modified PC masterbatch; 20-30 parts of modified ABS masterbatch; 2-7 parts of titanium silicon powder; 8-16 parts of hollow glass microspheres; 2 parts of toughening agent; 0.1-0.3 parts of lubricant; wherein the modified PC masterbatch is made by mixing PC resin, 2,6-di-tert-butyl-4-methylphenol, and thiodipropionic acid diester; wherein the modified ABS masterbatch is made by mixing ABS resin and composite ultraviolet absorber. It effectively improves the reflectivity of the lamp housing to light, reduces the amount of light absorbed by the lamp housing, and thus slows down the aging of the lamp.
[0006] The titanium silicon powder is obtained by combining silicon dioxide with titanium dioxide after surface treatment with a silane coupling agent to form a dense protective film on the surface of titanium dioxide.
[0007] The preferred technical solution is that the composite ultraviolet absorber is mixed with 46% of phenyl o-hydroxybenzoate, 23% of dihydroxybenzophenone, and 31% of 2-hydroxyphenyltriazine derivatives.
[0008] The specific composition of the modified PC masterbatch is: the mass proportion of PC resin is 98.6%, the mass proportion of 2,6-di-tert-butyl-4-methylphenol is 0.7%, and the mass proportion of thiodipropionic acid diester is 0.7%.
[0009] Preferably, in the modified ABS masterbatch, the mass proportion of ABS resin is 94.2%, and the mass proportion of the composite ultraviolet absorber is 5.8%.
[0010] A method for preparing a lamp housing using the composite material comprises the following steps: Step S10: uniformly mixing titanium silicon powder, hollow glass microspheres, a toughening agent, and a lubricant according to mass fractions to obtain a premix; Step S20: adding the modified PC masterbatch and the modified ABS masterbatch into a high-speed mixer according to the mass fraction for premixing, and then adding the premix in step S10 and continuing to mix for a period of time to obtain a final mixture; Step S30: adding the final mixture into a melting device and fully heating and stirring to obtain a molten material; Step S40: The molten material is poured and injected into a mold by a die-casting machine to obtain a lamp housing, which is then dried for later use.
[0011] Wherein, in step S20, the preparation steps of the modified PC masterbatch are as follows: step S21, PC resin, 2,6-di-tert-butyl-4-methylphenol, and thiodipropionic acid diester are fully mixed according to mass fractions, and granulated after extrusion through a screw extruder to form a modified PC masterbatch.
[0012] Further, in step S20, the preparation steps of the modified ABS masterbatch are as follows: step S22, the ABS resin and the composite UV absorber are fully mixed according to the mass fraction, wherein the composite UV absorber is pre-mixed by 46% of phenyl o-hydroxybenzoate, 23% of dihydroxybenzophenone, and 31% of 2-hydroxyphenyltriazine derivative, and then extruded by a screw extruder and granulated to form a modified PC masterbatch.
[0013] The anti-aging composite material for lamp housing of the present invention has the following technical effects: The anti-aging lamp shell composite material of the present application comprises, by mass fraction, the following components: 80-110 parts of modified PC masterbatch; 20-30 parts of modified ABS masterbatch; 2-7 parts of titanium silicalite powder; 8-16 parts of hollow glass microspheres; 2 parts of toughening agent; 0.1-0.3 parts of lubricant; the titanium silicalite powder effectively increases the white brightness of the lamp shell, and when used in conjunction with the hollow glass microspheres, the lamp shell can have a higher light reflectivity, so that the lamp shell reflects most of the light to the diffuser plate and then emits it, thereby increasing the overall luminous flux of the lamp, and at the same time, the lamp shell reduces the amount of light absorbed by the lamp shell, which can effectively slow down the aging rate.
[0014] The modified PC masterbatch is made of a mixture of PC resin, 2,6-di-tert-butyl-4-methylphenol, and thiodipropionic acid diester; the modified ABS masterbatch is made of a mixture of ABS resin and a composite UV absorber. Both PC and ABS masterbatches are modified to make the lamp housing have higher antioxidant properties after molding. Titanium silicon powder and composite UV absorbers can better absorb UV light and slow down the aging of lamps. The lamp housing is made of a mixture of PC masterbatches and ABS masterbatches, which greatly improves the overall toughness and impact resistance of the lamp, and also enhances its anti-aging ability. DETAILED DESCRIPTION
[0015] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention is clearly and completely described. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. It should be noted that the embodiments in this application and the features in the embodiments can be combined with each other arbitrarily without conflict.
[0016] The anti-aging lamp housing composite material and the method for preparing the anti-aging lamp housing are described in detail below in conjunction with a plurality of embodiments. Example 1
[0017] The present invention provides an anti-aging composite material for lamp housing, the components by mass fraction include: 80-110 parts of modified PC masterbatch; 20-30 parts of modified ABS masterbatch; 2-7 parts of titanium silicon powder; 8-16 parts of hollow glass microspheres; 2 parts of toughening agent; 0.1-0.3 parts of lubricant; wherein the modified PC masterbatch is made by mixing PC resin, 2,6-di-tert-butyl-4-methylphenol, and thiodipropionic acid diester; wherein the modified ABS masterbatch is made by mixing ABS resin and a composite ultraviolet absorber. It effectively improves the reflectivity of the lamp housing to light, reduces the amount of light absorbed by the lamp housing, and thus slows down the aging of the lamp. The titanium silicon powder is obtained by combining silicon dioxide with titanium dioxide after surface treatment with a silane coupling agent, and forming a dense protective film on the surface of titanium dioxide. Due to the presence of the silicon dioxide film, light cannot catalyze the reaction of titanium dioxide, which effectively reduces the photochemical activity of the titanium silicon powder. The addition of titanium silicon powder can increase the white brightness of the lamp shell, making the light reflection effect better. Hollow glass beads have a mirror reflection effect, and with titanium silicon powder as the background color, its reflection effect is better. At the same time, the addition of hollow glass beads makes the lamp shell have stronger impact resistance, while enhancing the sound insulation and heat insulation performance of the lamp shell, and reducing the aging effect of physical factors on the lamp shell. In this embodiment, modified PC masterbatch and modified ABS masterbatch are used to prepare PC / ABS plastic alloy, so that the overall strength and anti-aging performance of the lamp shell are improved. The modified PC masterbatch and modified ABS masterbatch are modified separately, so that the antioxidant and UV resistance of the lamp shell are greatly improved.
[0018] Preferably, in the modified ABS masterbatch, the mass proportion of ABS resin is 94.2%, and the mass proportion of the composite ultraviolet absorber is 5.8%. After repeated experiments, the ratio of the composite ultraviolet absorber was finally determined. The composite ultraviolet absorber is mixed with 46% of phenyl o-hydroxybenzoate, 23% of dihydroxybenzophenone, and 31% of 2-hydroxyphenyltriazine derivatives. The composite ultraviolet absorber composed of these three components can greatly delay the aging of the lamp housing, so that the lamp housing will not turn yellow and brittle after a longer period of use, and the service life of the lamp is greatly improved.
[0019] The specific composition of the modified PC masterbatch is that the mass proportion of PC resin is 98.6%, the mass proportion of 2,6-di-tert-butyl-4-methylphenol is 0.7%, and the mass proportion of thiodipropionic acid diester is 0.7%. The modified masterbatch method is used to pre-mix 2,6-di-tert-butyl-4-methylphenol and thiodipropionic acid diester into the PC masterbatch, so that the components are mixed more evenly during subsequent processing. The combination of the two components greatly improves the antioxidant performance of the lamp. Example 2
[0020] A method for preparing a lamp housing using the composite material includes the following steps: step S10: uniformly mixing titanium silicon powder, hollow glass microspheres, toughening agent, and lubricant according to mass fraction to obtain a premix; step S20: adding modified PC masterbatch and modified ABS masterbatch to a high-speed mixer for premixing according to mass fraction, and then adding the premix in step S10 to continue mixing for a period of time to obtain a final mixture; step S30: adding the final mixture to a melting device to fully heat and stir to obtain a molten material; step S40: the molten material is cast and injected into a mold by a die-casting machine to obtain a lamp housing, and then dried for standby use. The use of multiple premixing methods allows the various components to be mixed more evenly, and the overall quality of the lamp housing is better after it is prepared.
[0021] In step S20, the preparation step of the modified PC masterbatch is as follows: Step S21, PC resin, 2,6-di-tert-butyl-4-methylphenol, and thiodipropionic acid diester are fully mixed according to mass fractions, extruded through a screw extruder, and granulated to form a modified PC masterbatch. During mixing, the PC resin is heated to soften, fully premixed, added to the screw extruder, further stirred, and then extruded.
[0022] Further, in step S20, the preparation steps of the modified ABS masterbatch are as follows: step S22, the ABS resin and the composite UV absorber are fully mixed according to the mass fraction, wherein the composite UV absorber is pre-mixed by 46% of phenyl o-hydroxybenzoate, 23% of dihydroxybenzophenone, and 31% of 2-hydroxyphenyltriazine derivative, and then extruded by a screw extruder and granulated to form a modified PC masterbatch. Example 3
[0023] The composite material is prepared according to the weight of 1kg, and 5 parts of titanium silicon powder, 14 parts of hollow glass microspheres, 1.5 parts of toughening agent, and 0.3 parts of lubricant are uniformly mixed to obtain a premix; 100 parts of modified PC masterbatch and 25 parts of modified ABS masterbatch that have been modified are added to a high-speed mixer for premixing according to the mass fraction, and then the premix of titanium silicon powder and the like is added and mixed for a period of time to obtain the final mixture; the final mixture is added to the melting equipment and fully heated and stirred to obtain the molten material, the heating temperature is controlled between 230℃-240℃, and the stirring time is 20min. The molten material is cast and injected into the mold by a die-casting machine to obtain the lamp housing, which is dried for standby use. The lamp housing processing technology is consistent with the existing one. The final shell is subjected to light aging test. Example 4
[0024] This embodiment does not contain titanium silicon powder. The composite material is prepared according to a weight of 1kg. 14 parts of hollow glass microspheres, 1.5 parts of toughening agent, and 0.3 parts of lubricant are taken in proportion and mixed evenly to obtain a premix; 100 parts of modified PC masterbatch and 25 parts of modified ABS masterbatch that have been modified are added to a high-speed mixer for premixing according to the mass fraction, and then the premix of titanium silicon powder and the like is added and mixed for a period of time to obtain the final mixture; the final mixture is added to the melting equipment and fully heated and stirred to obtain a molten material, the heating temperature is controlled between 230℃-240℃, and the stirring time is 20min. The molten material is cast and injected into the mold by a die-casting machine to obtain the lamp housing, which is dried for use. The lamp housing processing technology is consistent with the existing one. The finally obtained housing is subjected to a light aging test. Example 5
[0025] This embodiment does not contain hollow glass microspheres. The composite material is prepared by weight of 1kg. 5 parts of titanium silicon powder, 1.5 parts of toughening agent, and 0.3 parts of lubricant are taken in proportion and mixed evenly to obtain a premix; 100 parts of modified PC masterbatch and 25 parts of modified ABS masterbatch that have been modified are added to a high-speed mixer for premixing according to mass fraction, and then the premix of titanium silicon powder and the like is added and mixed for a period of time to obtain the final mixture; the final mixture is added to the melting equipment and fully heated and stirred to obtain a molten material, the heating temperature is controlled between 230℃-240℃, and the stirring time is 20min. The molten material is cast and injected into the mold by a die-casting machine to obtain the lamp housing, which is dried for use. The lamp housing processing technology is consistent with the existing one. The finally obtained housing is subjected to light aging test. Example 6
[0026] The PC masterbatch and ABS masterbatch in this embodiment have not been modified. The composite material is prepared by weight of 1kg, and 5 parts of titanium silicon powder, 14 parts of hollow glass microspheres, 1.5 parts of toughening agent, and 0.3 parts of lubricant are taken in proportion and evenly mixed to obtain a premix; 100 parts of modified PC masterbatch and 25 parts of ABS masterbatch are added to a high-speed mixer for premixing according to mass fraction, and then the premix of titanium silicon powder and the like is added and mixed for a period of time to obtain the final mixture; the final mixture is added to the melting equipment and fully heated and stirred to obtain a molten material, the heating temperature is controlled between 230℃-240℃, and the stirring time is 20min. The molten material is cast and injected into the mold by a die-casting machine to obtain the lamp housing, which is dried for standby use. The lamp housing processing technology is consistent with the existing one. The finally obtained housing is subjected to light aging test. Example 7
[0027] This embodiment uses an existing PC lamp housing for aging testing as a control group.
[0028] The anti-UV aging test is carried out according to GB / T16422.3-2014 standard. The specific experimental method refers to the standard. The aging temperature is 60℃, and 500 hours is used as the benchmark test. The aging time of the lamp is increased by 100 hours each time. The strong light aging is carried out using LED light strips, with a strong light flux of 1Wlm and a test temperature of 50℃. After adding titanium silicalite, hollow glass microspheres and modifying the masterbatch, or PC and ABS alloys, the anti-aging performance can be improved, but the effect of adding titanium silicalite and hollow glass microspheres alone is not as good as the effect of adding both at the same time. The combination of the two complements each other to further improve the anti-aging performance.
[0029] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that an article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such article or device. In the absence of further restrictions, the elements defined by the sentence "include..." do not exclude the existence of other identical elements in the article or device including the elements.
[0030] The above embodiments are only used to illustrate the technical solution of the present invention and are not intended to limit the present invention. The present invention is described in detail with reference to the preferred embodiments. It should be understood by those skilled in the art that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, and should be included in the scope of the claims of the present invention.
Claims
1. An anti-aging composite material for a lamp housing, characterized in that: The components by mass fraction include: 80-110 parts of modified PC masterbatch; 20-30 parts of modified ABS masterbatch; 2-7 parts of titanium silicon powder; 8-16 parts of hollow glass microspheres; 2 parts of toughening agent; 0.1-0.3 parts of lubricant; The modified PC masterbatch is made by mixing PC resin, 2,6-di-tert-butyl-4-methylphenol and thiodipropionic acid diester; The modified ABS masterbatch is made by mixing ABS resin and a composite UV absorber.
2. The anti-aging composite material for lamp housing according to claim 1, characterized in that: The titanium silicon powder is obtained by combining silicon dioxide with titanium dioxide after surface treatment with a silane coupling agent to form a dense protective film on the surface of titanium dioxide.
3. The anti-aging composite material for lamp housing according to claim 1, characterized in that: The composite ultraviolet absorber is mixed with 46% of phenyl o-hydroxybenzoate, 23% of dihydroxybenzophenone and 31% of 2-hydroxyphenyltriazine derivative.
4. The anti-aging composite material for lamp housing according to claim 1, characterized in that: In the modified PC masterbatch, the mass proportion of PC resin is 98.6%, the mass proportion of 2,6-di-tert-butyl-4-methylphenol is 0.7%, and the mass proportion of thiodipropionic acid diester is 0.7%.
5. The anti-aging composite material for lamp housing according to claim 1, characterized in that: In the modified ABS masterbatch, the mass proportion of ABS resin is 94.2%, and the mass proportion of the composite ultraviolet absorber is 5.8%.
6. A method for preparing an anti-aging lamp housing, characterized in that: Made of the composite material according to any one of claims 1 to 5; The method comprises the following steps: Step S10: uniformly mixing titanium silicon powder, hollow glass microspheres, toughening agent and lubricant according to mass fraction to obtain a premix; Step S20: adding the modified PC masterbatch and the modified ABS masterbatch into a high-speed mixer according to the mass fraction for premixing, and then adding the premix in step S10 and continuing to mix for a period of time to obtain a final mixture; Step S30: adding the final mixture into a melting device and fully heating and stirring to obtain a molten material; Step S40: The molten material is poured and injected into a mold by a die-casting machine to obtain a lamp housing, which is then dried for later use.
7. The method for preparing an anti-aging lamp housing according to claim 6, characterized in that: In step S20, the preparation steps of the modified PC masterbatch are as follows: step S21, PC resin, 2,6-di-tert-butyl-4-methylphenol, and thiodipropionic acid diester are fully mixed according to mass fractions, and granulated to form modified PC masterbatch after extrusion through a screw extruder.
8. The method for preparing an anti-aging lamp housing according to claim 6, characterized in that: In step S20, the preparation steps of the modified ABS masterbatch are as follows: step S22, the ABS resin and the composite UV absorber are fully mixed according to the mass fraction, wherein the composite UV absorber is pre-mixed by 46% of phenyl o-hydroxybenzoate, 23% of dihydroxybenzophenone, and 31% of 2-hydroxyphenyltriazine derivative, and then extruded by a screw extruder and granulated to form a modified PC masterbatch.
Citation Information
Cited By
PC anti-ultraviolet anti-aging master batch as well as preparation method and application thereof
CN120842824A